1994
DOI: 10.1111/j.1095-8649.1994.tb01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary indices of stress in the progeny of rainbow trout (Oncorhynchus mykiss) selected for high and low responsiveness to stress

Abstract: A series of pooled gamete matings was carried out employing eggs and milt from mature male and female rainbow trout selected for a consistently high‐ or low‐responsiveness to stress, as indicated by post‐stress plasma cortisol elevation. Development of the progeny was closely monitored and the responsiveness to stress of the progeny of high‐responding parents and the progeny of low‐responding parents was assessed by two methods. For a period of 14 months, at approximately monthly intervals, the plasma cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…However, it is difficult to assess which element of the combined stressor is most important in evoking this response. Similar observations were made during a previous study with rainbow trout selected for stress responsiveness (Pottinger et al, 1994b) and has been confirmed during a recent study with the same F2 lines (T. G. Pottinger and K. G. T. Pulman, unpublished observations). Further investigations are being made to establish whether the dynamics of change in plasma cortisol levels during stress in the HR and LR F2 lines has altered radically from that observed in the F1 lines.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is difficult to assess which element of the combined stressor is most important in evoking this response. Similar observations were made during a previous study with rainbow trout selected for stress responsiveness (Pottinger et al, 1994b) and has been confirmed during a recent study with the same F2 lines (T. G. Pottinger and K. G. T. Pulman, unpublished observations). Further investigations are being made to establish whether the dynamics of change in plasma cortisol levels during stress in the HR and LR F2 lines has altered radically from that observed in the F1 lines.…”
Section: Discussionsupporting
confidence: 89%
“…The reasons for this are unclear but may be related to the age, size or strain of the carp used in Experiment 2 which were different to those used in Experiments 1 and 3. The stress responsiveness of salmonid fish can vary between strains (Pickering & Pottinger, 1989;Pottinger & Moran, 1993;Pottinger et al, 1994) and the same is likely to be true of non-salmonid fish. There have been no reports that age and size are factors which affect stress responsiveness in fish although that possibility cannot be discounted.…”
Section: Effects Of Capture and Confinement On Plasma Cortisol Levelsmentioning
confidence: 99%
“…Recent studies have demonstrated that the stress responsiveness of individual rainbow trout, measured as the magnitude of increase in blood cortisol levels following exposure to a standardised confinement stressor, is to a large extent an individual characteristic (Pottinger et al, 1992(Pottinger et al, , 1994) with a moderate to high degree of heritability (Fevolden et al, 1999; offering the prospect of selection for stress tolerant fish. However, it is not yet known at what site(s) within the hypothalamus-pituitary-interrenal (HPI) endocrine cascade selection for responsiveness operates.…”
Section: Introductionmentioning
confidence: 99%